FEATURES OF DENTITION AND OCCLUSION IN PATIENTS WITH CLEFT LIP AND PALATE - Панахов Н. А.,; Гасанлі Е. Я.,; Гасанлі, Н.С. (World of Medicine and Biology, 2015)
The purpose of the study was to study the state of dentition and occlusion in persons with congenital cleft lip and palate. Material and methods. We examined 68 patients with congenital cleft lip and palate who applied to the Dental Clinic of the Azerbaijan Medical University, residing in Baku and other cities and districts of Azerbaijan Republic. Using alginate material were taken casts of the upper and lower jaws of patients to and from solid plaster cast diagnostic models. Design 136 models. For an objective assessment of the closure of dentition in a state of Central occlusion was applied the method of occlusivity. Diagnostic models have been studied in three mutually perpendicular directions. Thus first measured the teeth and dental rows assessed separately. Identified abnormal positioning of teeth, the transverse dimensions of the dental arch distance between the canines, the length of the anterior segment, size of apical base, dental arch form, balance of space, the offset of the center line in the millimeter value, the depth of curve of Spee in the mandible. In the next phase, it was found bioclusive ratio. This examined the proportionality of the teeth upper and lower jaw, found the class of the closure of the first molar and the canines on Anglo, matched transverse sizes of the dental arches, the vertical overlap of the incisors, the presence of disocclusion in the anterior and lateral parts of the dentition. Results and discussion. Biometric analysis of models of the jaws the patients in condition of Central occlusion showed that in patients, mainly formed with a reverse incisal overlap and one or two - double-sided cross bite. When the closure 13 and 43, and 23 and 33 teeth ratio Anglu was within the third class, and the gnashing of 16 and 46, 26 and 36 and the teeth – class II. This, in our opinion, is the result of ectopic eruption of teeth 16 and 26. Biometric analysis of models of patients undergoing unilateral nonunion of the upper lip and palate, showed that almost all patients are absent 12 or 22 teeth on the side of the cleft, occasionally absent 11 or 21 teeth. Half of the patients had microdontia upper front teeth, you can say almost all the patients were anomalies of position of upper anterior teeth, premolars and molars. On the healthier side of anomalies of dentition met three times smaller cases. On models of patients compared with the norm of transverse and longitudinal dimensions of the dentition. In all cases when compared with the normal dentitions of patients were smaller. But the main difference is felt in the field of 13 and 23 teeth, the narrowness of the upper jaw was even more. When compared with the norm in the field of 16 and 26 teeth, the difference was less expressed. Surgery for cleft lip and palate is not very affected on the difference of the dimensions of the dental arches in the lower jaw. Conclusions. The condition encountered in patients with congenital cleft lip and palate, occlusion of the jaws, leading to decreased mastication efficiency. As the narrowing and shortening of the dentition leads to the reduction of the total occlusal area of the teeth, and thereby to reduce the contact area between the teeth and the antagonists. At the same time, because of a violation of fissure-papulose ratio of teeth, broken and also the biomechanics of the lower jaw, there are obstacles to the movement of the jaw in different directions. The resulting locking of the muscles, responding adaptively, thereby aggravate the situation.
Keywords: cleft lip and palate; dentofacial anomalies; teeth; dentitions; occlusion; bite